(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Investigate the effect of research project course on nursing students’ attitude toward research at a college of nursing in Kerbala University and identify the relationship between nursing student’ attitude and demographic variables. A pre-experimental design (One-group Pretest-Posttest design) was utilized to determine the effect of research project course on nursing students’ attitude toward research at a college of nursing in Kerbala University. All participants were exposed to assess of attitudes regarding research before and after the implementation of the research project course in order to detect the effect of the course. The current study results revealed that; the majority (74.2%) of nursing students were within age groups (20- 22) years old the mean age of the all students was (22.27) years. 82.3% of total students were female. the majority (82.3%) of subjects were single, most of sample (80.6%) were urban resident, the mean of score of the positive attitude of respondents in posttest of the research project course was significantly higher than the pretest of the research project course in all aspects of attitude regarding research project course, and no significant difference between the nursing students’ demographic variables and attitude responses in the posttest of research project course.